Coping with the invisible impacts of COVID-19 in a context of polycrises: wellbeing strategies of marginalised urban and Indigenous Brazilian youth - Börner, Susanne; Giatti, Leandro; Bizzotto, Luciana; Rocha El-Kadri, Michele; Sousa Reis, Ana Elizabeth; Schweickardt, Júlio Cesar; Kraftl, Peter; Andres, Lauren (Frontiers in Psychology, 2025)
The wellbeing of young people in Brazil is significantly impacted by interconnected challenges such as local and global inequalities, violence, the climate emergency, a loss of ancestral identity, and the increasing precarity of education and employment. These overlapping crises influence how young people make sense of their everyday lives, envision their futures, and adapt to wellbeing challenges. Public policies continue to inadequately address immediate and long-term wellbeing needs and local realities of youth in situations of vulnerability. Combining data from two research projects in São Paulo and the Brazilian Amazon, we explore the lived experiences and adaptive wellbeing strategies of marginalised Brazilian youth across urban and Indigenous communities during and after COVID-19 pandemic, based on youth-led survey data and participatory research. The article makes an important contribution to the field by proposing a decolonial counter-narrative to dominant Western understandings of youth wellbeing. Guided by the confluence of diverse worldviews from the margins, specifically Indigenous and urban Brazilian youth from the periphery, the article advances understandings of youth-led mental health from the perspective of the relational concept and practice of “bem viver” (“good life”). Results indicate that although youth mental health challenges, including anxiety and depression, were exacerbated during and after the COVID-19 pandemic. Youth however developed individual and collective youth-led self-care strategies. These were grounded in local realities recognizing solidarity, reciprocity, and interconnectedness as important pillars to maintain emotional stability and feel connected to others and the world around them. We recommend that interventions and policies to improve young people's inner states of wellbeing need to go hand in hand with community-oriented wellbeing strategies led by the principles of bem viver for collectively reimagining their futures.